STRATEGIC DILEMMAS IN THE FACE OF GLOBAL TURMOIL: GEOPOLITICAL TENSIONS AS FORMIDABLE ADVERSARIES TESTING THE RESILIENCE OF CONTEMPORARY BUSINESS LANDSCAPES - I Dewa Gede Sayang Adi Yadnya; Arie Fitria; Nanang Yusroni; Loso Judijanto; Edi Putra Berutu (Adisam Publisher, 2023)
In scrutinizing the intricate fabric of the global landscape, this research thoroughly investigated the strategic dilemmas that businesses grapple with amid the formidable challenges stemming from geopolitical tensions. The central focus was on evaluating the resilience of contemporary business landscapes, seeking to unravel the intricate and multifaceted relationship between organizations and the ever-evolving geopolitical forces that shape the global stage. The research methodology was robust and comprehensive, incorporating a detailed literature review that provided a foundational understanding, theoretical frameworks that lent conceptual depth, and empirical findings that brought practical insights to the forefront. This triangulated approach aimed to capture the complexity and nuances inherent in business relationships and geopolitical dynamics. Going beyond the realm of passive observation, the study probed into the proactive strategies organizations adopt to confront, navigate, and overcome the challenges arising from geopolitical uncertainties. By synthesizing a diverse array of perspectives, the research sought to shed light on the strategic responses embraced by businesses. In doing so, it aimed to push the boundaries of contemporary business resilience, exploring how organizations innovate and adapt in the face of the turbulence induced by global turmoil. In essence, this research contributes to a deeper comprehension of the intricate dance between businesses and geopolitical forces, offering valuable insights into the strategic choices underpinning organizational resilience amid the complex global dynamics of our times.